LINKING SCHOOL FINANCIAL MANAGEMENT TO EDUCATIONAL EFFECTIVENESS - Bambang Sigit; Karwanto Karwanto; Dany Sulistiono; Riinawati Riinawati; Rusnadi Rusnadi (PEDAGOGIK : JURNAL PENDIDIKAN, 2026)
This study aims to analyze school financial management and its role in improving educational effectiveness. The approach is descriptive qualitative, with data collected through semi-structured interviews and financial document analysis. Data analysis was conducted through data reduction, presentation, and drawing conclusions, with validity maintained through source triangulation. The results indicate that budget planning is carried out collaboratively based on program needs, budget implementation follows structured administrative procedures, and accountability is realized through systematic reporting supported by transaction evidence. Good financial management contributes to the smooth running of programs and operational support for learning. Educational effectiveness is evident in the implementation of activities and the availability of facilities, but the link between budget policies and improved learning quality remains underdeveloped. This study recommends strengthening the orientation of budget planning towards learning development and increasing transparency to encourage school community participation.